2019
DOI: 10.1002/advs.201901788
|View full text |Cite
|
Sign up to set email alerts
|

3D Printing of Solution‐Processable 2D Nanoplates and 1D Nanorods for Flexible Thermoelectrics with Ultrahigh Power Factor at Low‐Medium Temperatures

Abstract: graphene, [10] conductive polymer, and hybrids, [11] have the ability to interconvert thermal to electrical energy without moving parts. These f-TEGs can be integrated with portable/wearable electronics and sensors, and enable selfpowered devices. In this context, V 2 -VI 3 metal chalcogenides (Bi 2 Te 3 , Sb 2 Te 3 , and related alloys and compounds) [1,[12][13][14][15][16][17] have attracted particular attention because of their high figure of merit (ZT) near room temperature. [18] For example, p-type Bi 2 T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 55 publications
0
28
0
Order By: Relevance
“…However, it is difficult to obtain complex shapes through conventional methods such as hot pressing, spark plasma sintering, and zone melting. 140 So far, SLA, 141 FDM, 142,143 SLS, 144 DIW, [145][146][147][148] SLM, [149][150][151][152] 3D printing technologies have been investigated for the preparation of TE devices.…”
Section: 52mentioning
confidence: 99%
“…However, it is difficult to obtain complex shapes through conventional methods such as hot pressing, spark plasma sintering, and zone melting. 140 So far, SLA, 141 FDM, 142,143 SLS, 144 DIW, [145][146][147][148] SLM, [149][150][151][152] 3D printing technologies have been investigated for the preparation of TE devices.…”
Section: 52mentioning
confidence: 99%
“…Ou et al fabricated a TEG made from Sb 2 Te 3 nanoflakes and carbon nanotubes with a power factor of ≈41 μWm −1 K −2 using a modified aerosol-jet printing method [ 96 ]. Dun et al used this 3D conformal aerosol printing of solution-processed p-type Sb 2 Te 3 to print flexible TEG with a high power factor of 2.2 mWm −1 K −2 at 500 K [ 97 ]. Figure 10 illustrates the 3D aerosol jet printing of p-type Sb 2 Te 3 .…”
Section: Various Synthesis and Fabrication Techniques For Large-scale Productionmentioning
confidence: 99%
“… Schematic illustration of aerosol printing. Reproduced with permission from [ 97 ]. Copyright Wiley Online Library, 2019.…”
Section: Figurementioning
confidence: 99%
“…Many studies have reported inorganic TE slurries/powders that can be printed by SLM/SLS, 43,45,46 DIW [47][48][49] or stereolithography 50 to form ingots. Furthermore, the same materials can be formulated as inks, which can be directly painted onto 3D objects [51][52][53] or patterned on flexible substrates by inkjet printing, 42,54 aerosol jet printing, 53,55,56 dispensing, 57 or screen printing 52,[58][59][60][61][62][63][64] to form shape-conformable and flexible devices. However, the combination of those printing techniques with the search of morphological anisotropy to improve the final performance has been largely overlooked.…”
Section: Printed Anisotropic Inorganic Thermoelectric Materialsmentioning
confidence: 99%